Minerals Beneficiation - Adsorption of Calcium, Magnesium, and Sodium Ion by Quartz - S. W. Clark; S. R. B. Cooke (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Adsorption of calcium and magnesium by quartz was determined over a wide pH range using flame photometry for solution analysis. A parallelism was noted between calcium adsorption at alkaline pH and flotation of activated quartz by means of various fatty acid collectors. Abstraction of calcium from 100 ppm solutions increased above pH 10.5 until all of the calcium was removed at pH values between 12 and 12.5. Calcium was desorbed from the quartz over the pH range 12.5 to 13.0 and returned to the solution. Precipitation of magnesium hydroxide prevented measurement of magnesium adsorption above a pH of 9.9. A calcium adsorption isotherm determined at pH 9 matched measurements of barium adsorption by other investigators over the range where adsorption corresponded to the equation of a Freundlich adsorption isotherm. In accordance with the Gouy-Chapman theory for adsorption in the diffuse layer, adsorption of the divalent cations under these conditions was four times the adsorption of monovalent sodium. Activation of quartz by multivalent metal cations in flotation using anionic collectors has been studied by many investigators. The occurrence of activator cations in the water of flotation mills makes depression of silaceous gangue very difficult. Alternatively, in some flotation systems it is practical to cause activation of quartz so that it is floated from the desirable mineral values. The present study was initiated to investigate the activation of quartz by measuring adsorption of calcium and magnesium ions as a function of solution pH. Early empirical tests showed that quartz would be activated to flotation using anionic collectors if any of a number of divalent or trivalent metallic cations were present in the pulp.1*2 Subsequent studies by Clemmer,3 Cooke and Digre,4 Cooke,5 Schuhmann and Prakash,6 and Cooke, Iwasaki, and Choi,7-8 showed that flotation depended strongly upon the alkalinity of the flotation pulp, the concentration of the activating cations, and the chain length and structure of the organic collectors used. The concept of the electrical double layer has been applied to the case of the quartz-aqueous solution interface by Gaudin and Fuerstenau,9-10 and by de Bruyn 11 to explain the activation of quartz by multivalent metal cations. Studies of the surface of quartz by Gaudin and Fuerstenau9,10,12 and by Li " using the streaming potential technique contributed much information on the electro kinetic condition of the surface of quartz in the presence of various organic and inorganic ions. Measurement of adsorption of ac-